Male Resistance to Gender Bias in Professions: Analysis of Najwa Shihab's "Enaknya Jadi Laki-Laki" - Rifqi, Naflah; 'Athiyyah, Avita Aniqotul (Proceeding of International Conference on Engineering, Technology, and Social Sciences (ICONETOS), 2025)
In the professional field in particular, women still experience a lot of subordination discrimination and negative stereotypes. This was raised by the YouTube video content “Enaknya Jadi Laki-Laki” published on December 28, 2023 on the Najwa Shihab channel. However, in reality there are also disadvantages felt by men for the demands of their work and gender. Through a qualitative approach with discourse analysis, this research focuses on revealing men's resistant responses to the issues raised in the issue of gender equality in the professional field in the Youtube video. The study analyzed 1115 comments with 38.7% of the comments showing negative sentiments, and 12.37% of them expressing resistance to the claims discussed by the speakers. The results of the analysis show that this resistance appears in the form of arguments criticizing data that are considered assumptions, the presentation of 'lame' content between male and female speakers, and the need to understand the biological differences between men and women in certain job specifications, some comments also indicate the complexity of aspects to achieve true gender equality. This study makes an important contribution in understanding the dynamics of inter-gender resistance in the context of public media, especially in efforts to fight for better gender equality through information and communication that is educative and multi-perspective, so that gender mainstreaming efforts can create good equality for all parties.